The prevalence and clinical significance of EGFR mutations in non-small cell lung cancer patients in Egypt: a screening study - Asmaa A. Helal; Ibrahim H. Kamal; Ahmed Osman; Magdy Youssef; Adel K. Ibrahim (Journal of the Egyptian National Cancer Institute, 2024)
Abstract Background Lung cancer is a form of cancer that is responsible for the largest incidence of deaths attributed to cancer worldwide. Non-small cell lung cancer (NSCLC) is the most prevalent of all the subtypes of the disease. Treatment with tyrosine kinase inhibitors (TKI) may help some people who have been diagnosed with non-small cell lung cancer. The presence of actionable mutations in the epidermal growth factor receptor (EGFR) gene is a key predictor of how a patient will respond to a TKI. Thus, the frequency of identification of mutations in EGFR gene in patients with NSCLC can facilitate personalized treatment. Objective The objective of this study was to screen for mutations in the EGFR gene and to investigate whether there is a correlation between the screened mutations and various clinical and pathological factors, such as gender, smoking history, and age, in tissue samples from patients with NSCLC. Methods The study comprised 333 NSCLC tissue samples from 230 males and 103 females with an average age of 50 years. Exons 18–21 of the EGFR gene have been examined using real-time PCR. Using SPSS, correlations between clinical and demographic variables were examined, and EGFR mutation and clinical features associations were studied. Results The study’s findings revealed that the incidence rate of EGFR mutation was 24.32% (81/333), with partial deletion of exon 19 (19-Del) and a point mutation of L858R in exon 21 accounting for 66.67% (P < 0.001) and 28.40% (P < 0.001) of the mutant cases, respectively. Patients who had the T790M mutation represent 4.94% (P = 0.004) of total number of patients. Females harbored EGFR mutations (54.32%) with higher frequency than men (45.68%) (P < 0.001), while nonsmokers had EGFR mutations (70.37%) more frequently than current smokers (29.63%) (P < 0.001). Conclusion The screening study conducted in Egypt reported that the EGFR mutations prevalence was 24.32% among Egyptians with NSCLC. The study also found a slight gender bias, with females having an incidence rate of these mutations higher than males. Additionally, nonsmokers had higher rates of mutations in EGFR gene compared to smokers. According to the findings, somatic EGFR mutations can be employed as a diagnostic tool for non-small cell lung cancer in Egypt, and they can be implemented in conjunction with clinical criteria to identify which patients are more likely to respond favorably to TKIs.